X-ray induces mechanical and heat allodynia in mouse via TRPA1 and TRPV1 activation - Cun-Jin, Su (Mol Pain, 2019)
Radiotherapy-related pain is a common adverse reaction with a high incidence among cancer patients undergoing radiotherapy and remarkably reduces the quality of life. However, the mechanisms of ionizing radiation-induced pain are largely unknown. In this study, mice were treated with 20 Gy X-ray to establish ionizing radiation-induced pain model. X-ray evoked a prolonged mechanical, heat, and cold allodynia in mice. Transient receptor potential vanilloid 1 and transient receptor potential ankyrin 1 were significantly upregulated in lumbar dorsal root ganglion. The mechanical and heat allodynia could be transiently reverted by intrathecal injection of transient receptor potential vanilloid 1 antagonist capsazepine and transient receptor potential ankyrin 1 antagonist HC-030031. Additionally, the phosphorylated extracellular regulated protein kinases (ERK) and Jun NH2-terminal Kinase (JNK) in pain neural pathway were induced by X-ray treatment. Our findings indicated that activation of transient receptor potential ankyrin 1 and transient receptor potential vanilloid 1 is essential for the development of X-ray-induced allodynia. Furthermore, our findings suggest that targeting on transient receptor potential vanilloid 1 and transient receptor potential ankyrin 1 may be promising prevention strategies for X-ray-induced allodynia in clinical practice.